Long-lasting masculinizing effects of postnatal androgens on myelin governed by the brain androgen receptor. - Charly Abi Ghanem; Cindy Degerny; Rashad Hussain; Philippe Liere; Antoine Pianos; Sophie Tourpin; René Habert; Wendy B Macklin; Michael Schumacher; Abdel M Ghoumari (PLoS Genetics, 2017)
The oligodendrocyte density is greater and myelin sheaths are thicker in the adult male mouse brain when compared with females. Here, we show that these sex differences emerge during the first 10 postnatal days, precisely at a stage when a late wave of oligodendrocyte progenitor cells arises and starts differentiating. Androgen levels, analyzed by gas chromatography/tandem-mass spectrometry, were higher in males than in females during this period. Treating male pups with flutamide, an androgen receptor (AR) antagonist, or female pups with 5α-dihydrotestosterone (5α-DHT), revealed the importance of postnatal androgens in masculinizing myelin and their persistent effect into adulthood. A key role of the brain AR in establishing the sexual phenotype of myelin was demonstrated by its conditional deletion. Our results uncover a new persistent effect of postnatal AR signaling, with implications for neurodevelopmental disorders and sex differences in multiple sclerosis.